Ocena ranljivosti slovenskega obalnega pasu in njegova kategorizacija z vidika (ne)dopustnih posegov, dejavnosti in rabe - Turk, Robert (Annales. Series historia naturalis, 1999)
The Slovene coastal belt is in view of its natural and cultural riches a unique as well as highly fragile entity. In the last few decades it has been marked with intense littoralisation, i. e. distinct settling and speeded up development of various branches of economy and, in turn, with intense degradation of natural riches on both sides of the coastline. The article deals with the existing state of the Slovene coastal belt from the aspect of the preservation of natural riches as well as from existing activities and human pressures exerted upon it. The entire coastal belt and its ...
Keywords: environmental protection; obrežni pas; raba prostora; ranljivost; Slovenian Istria; Slovenska Istra; sonaravni razvoj; varstvo narave